1997
DOI: 10.1017/s0266078400009433
|View full text |Cite
|
Sign up to set email alerts
|

Pronouncing English in Brazil

Abstract: The impact and implications of British and American pronunciation models in South America's largest country

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Earlier research conducted in Brazil also found that EFL learners' oral production shift between American and British English (Mompean, 1997). In Brazil during the 1990s, American and British English were both recognized with equal status.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Earlier research conducted in Brazil also found that EFL learners' oral production shift between American and British English (Mompean, 1997). In Brazil during the 1990s, American and British English were both recognized with equal status.…”
Section: Literature Reviewmentioning
confidence: 86%
“…At this point, proper pronunciation is essential. Although there have been numerous studies on pronunciation in foreign language learning, they have primarily focused on English as a foreign language pronunciation (see, for example, Abugohar Mompean, 1997;Vančová, 2019;Wahyuningsih & Afandi, 2020). In other words, to the best of our knowledge, studies examining how words of Indonesian as a foreign language are pronounced by speakers of other languages are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Ao se falar em ensino de língua estrangeira no contexto educacional brasileiro, a primeira língua que naturalmente nos vem à mente é a língua inglesa, devido à sua predominância como língua estrangeira ensinada nas escolas brasileiras, um reflexo da condição hegemônica dessa língua no cenário internacional. As escolas, tanto públicas quanto privadas, na sua grande maioria, adotam o inglês como a única ou uma das línguas estrangeiras ministradas (Mompean, 1994).…”
Section: Considerações Iniciaisunclassified